ANALISIS KEMAMPUAN KOGNITIF DAN SIKAP SISWA PADA MATERI SISTEM REPRODUKSI MANUSIA KELAS XI IPA SMA NEGERI 1 TANJUNG MORAWA T.P 2016/2017 - Jessika Rajagukguk; Ashar Hasairin; Nurhayati Hutagaol (Jurnal Pelita Pendidikan, 2017)
This study aims to find the learning outcome and attitudes on material of humans reproductive system in grade XI IPA SMA Negeri 1 Tanjung morawa Learning Year 2016/2017. The population in this study were all students of class XI IPA which amounted to 78 people. 39 samples taken by purposive sampling in class XI  IPA 5 and 39 samples from each classes were taken by purposive sampling. The datas were collected by observasion sheets were used to know students attitudes and 30 question were used to get learning outcome the student The results showed that the percentage of cognitive aspect ability was good with the average score of 72,08. This can be seen from the presentation of the complete value of 75.64% with the categories of material and unfinished presentation as much as 24.53% with less understood category. While the presentation of student attitudes is good where the material assessment consisting of the following 5 categories of assessment indicators can be elaborated as follows: presentation of attitudes value to respect as much as 80.68%, presentation of attitudes value for responsibilities of 75.08%, presentation of values Attitudes for discipline as much as 81.97%, presentation attitudes to work together as much as 70.35% and presentation of attitude values for liveliness as much as 60.81%.Keywords: cognitive aspect ability, student attitudes, human reproductive system.